Contested Politics of Educational Reform in India: Aligning Opportunities with Interests - Manisha Priyam (Oxford University Press, 2015)
This book analyses the role of politics in the process in education policy reforms in the context of developing countries, specifically India. Considered significant in the real world, politics is missed out by the dominant approaches used to design or analyse the policy process. In the small body of analytical literature available, politics is viewed in a negative way, merely as an obstruction, which leads to failure of technically well designed policies However, if we focus also on cases of success, and view changes 'downstream' as poor people experience them, the reform-politics relationship unravels as a far more nuanced and deeply contested process. Comparing the case of educational policy reform in two Indian states of Andhra Pradesh and Bihar, this book finds that teachers and their unions need not necessarily work as collective actors to block reforms; neither does decentralization prove to be the panacea that a more technical understanding of reforms promotes. Unintended policy consequences, building allies amongst teachers, and a preference for collaboration with unions over more conflictual approaches, are possible reasons for better outcomes in Andhra. In comparison, the stagnation in Bihar has been on account of weaker policies of teacher management, and elite capture of local institutions. Seeing the change process, in terms of the day-to-day conditions of policy-implementation, helps in understanding the locally embedded nature of power relations within which schools for the poor work, and policy change unfolds. Often, policy gains may be contingent outcomes of leaders pursuing their own goals, while they seemingly work in the name of the poor. This book engages with the big world or power without necessarily romanticizing the local, and understands that the empirical reasons why the pursuit of the basic right to education remains a struggle for the poor.